Effects of spark plasma sintering on enhancing the thermoelectric performance of Hf–Ti doped VFeSb half-Heusler alloys. (March 2021) - El-Khouly, A.; Adam, A.M.; Novitskii, A.; Ibrahim, E.M.M.; Serhiienko, I.; Nafady, Ayman; Kutzhanov, M.K.; Karpenkov, D.; Voronin, A.; Khovaylo, V.
Abstract: This work presents a study on the thermoelectric properties of ultrafine grained Hf–Ti dual-doped VFeSb half-Heusler (HH) alloys treated by spark plasma sintering (SPS) at different temperatures. The concerned alloys were successfully synthesized by arc/induction melting and mechanical alloying (MA). Thermoelectric (TE) properties of Fe(V0.8 Hf0.2 )1- x Ti x Sb ( x  = 0.0, 0.2, 0.4) HH samples were studied over the temperature range from 100 to 900 K. Hf and Ti as heavy elements were used as dopants to create point defects aiming to reduce the material's thermal conductivity by enhancing the phonon scattering. Since the transport properties of HH alloys are sensitive to heat treatment, the effect of sintering temperature is studied as well. It was found that the power factor is significantly improved by increasing the sintering temperature. As a result, the figure of merit was enhanced by ~10% for the Fe(V0.8 Hf0.2 )0.8 Ti0.2 Sb sample and by ~30% for the Fe(V0.8 Hf0.2 )0.6 Ti0.4 Sb sample which were sintered at 1123 K, compared to those sintered at 1023 K. The maximum value was recorded at 0.33 for the sample Fe(V0.8 Hf0.2 )Sb. This value is higher than that of the singly doped FeV0.9 Hf0.1 Sb sample with a maximum zT value of 0.08. Also, it is higher than the reported value of the FeVSb doped with Ti which shows maximum ZT of 0.174 calculated for FeV0.7 Ti0.3 Sb at 658 K. Graphical abstract: Image 1 Highlights: A cost-effective and easy method is conducted for heat treatment. The power factor is significantly improved as high for samples which prepared at optimized sintering temperature. Notabl a reduction of lattice thermal conductivity due to stronger point defect scattering is achieved achived during Hf–Ti dual-doping. Significant enhancement in thermoelectric figure of merit (zT) is achieved at optimized sintering temperature at 1123 K.